Microfiche digitization and retrieval process improvement for the human relations area files collection of the Rizal library, Ateneo de Manila University - Dela Cruz, Tommy M. (2018)
This project converted the microfiche copy of the Human Relations Area Files (HRAF) collection of the Rizal Library to PDF format. The HRAF is a primary source of more than 300 cultures and societies around the world and serves anthropologists and other related scientists.